MARIA CALLAS W DRAMACIE MARIA CALLAS. LEKCJA ŚPIEWU TERRENCE’A MCNALLY’EGO I W POWIEŚCI WIELKI BAGAROZY HELMUTA KRAUSSERA - Pilipowicz, Andrzej (Acta Neophilologica, 2011)
The text deals with Maria Callas and with the connections of art and love, fame, cognisance and death. Callas is shown as a person whose voice builds a space turning the auditors into the characters that are evoked by her singing and made of human emotions. That is the way the people not only meet themselves but also discover some parts of their nature that they could not get known in the real world.